Simulated microgravity attenuates skin wound healing by inhibiting dermal fibroblast migration via F‐actin/YAP signaling pathway - Zhou, Yuhao; Lv, Wenjun; Peng, Xiufen; Cheng, Yansiwei; Tu, Yun; Song, Guanbin; Luo, Qing (Journal of cellular physiology, 2023)
Skin and its cell components continuously subject to extrinsic and intrinsic mechanical forces and are mechanical sensitive. Disturbed mechanical homeostasis may lead to changes in skin functions. Gravity is the integral mechanical force on the earth, however, how gravity contributes to the maintenance of skin function and how microgravity in space affects the wound healing are poorly understood. Here, using microgravity analogs, we show that simulated microgravity (SMG) inhibits the healing of cutaneous wound and the accumulation of dermal fibroblasts in the wound bed. In vitro, SMG inhibits the migration of human foreskin fibroblast cells (HFF‐1), and decreases the F‐actin polymerization and YAP (yes‐associated protein) activity. The SMG‐inhibited migration can be recovered by activating YAP or F‐actin polymerization using lysophosphatidic acid (LPA) or jasplakinolide (Jasp), suggesting the involvement of F‐actin/YAP signaling pathway in this process. In SMG rats, LPA treatment improves the cutaneous healing with increased dermal fibroblasts in the wound bed. Together, our results demonstrate that SMG attenuates the cutaneous wound healing by inhibiting dermal fibroblast migration, and propose the crucial role of F‐actin/YAP mechano‐transduction in the maintenance of skin homeostasis under normal gravity, and YAP as a possible therapeutic target for the skin care of astronauts in space.